Comparative effects of dietary functional nutrients on growth performance, meat quality, immune responses, and stress biomarkers in broiler chickens raised under heat stress conditions - Kim, Deok Yun; Kim, Jong Hyuk; Choi, Won Jun; Han, Gi Ppeum; Kil, Dong Yong (Animal bioscience, 2021)
Objective: The objective of the present study was to investigate the comparative effects of dietary functional nutrients including glutamine (Gln), chromium picolinate (Cr picolinate), vitamin C (Vit C), betaine (Bet), and taurine (Tau) on growth performance, meat quality, immune responses, and stress biomarkers in broiler chickens raised under heat stress conditions.Methods: A total of 420 21-d-old Ross 308 male broiler chickens (initial body weight = 866±61.9 g) were randomly allotted to 1 of 7 treatment groups with 6 replicates. One group was kept under thermoneutral conditions and was fed a basal diet (PC, positive control). Other 6 groups were exposed to a cyclic heat stress condition. One of the 6 groups was fed the basal diet (NC, negative control), whereas 5 other groups were fed the basal diet supplemented with 0.5% Gln, 500 ppb Cr picolinate, 250 mg/kg Vit C, 0.2% Bet, or 1.0% Tau. The diets and water were provided ad libitum for 21 d.Results: Broiler chickens in NC group had decreased (p<0.05) growth performance and immune responses measured based on cutaneous basophil hypersensitivity (CBH), but increased (p<0.05) stress responses measured based on feather corticosterone concentrations and blood heterophil:lymphocyte than those in PC group. However, none of dietary functional nutrients had a positive effect on growth performance of broiler chickens. Dietary supplementation of 250 mg/kg Vit C improved (p<0.05) CBH responses of broiler chickens, but other functional nutrients had no such an improvement in CBH responses. All functional nutrients decreased (p<0.05) stress responses of broiler chickens.Conclusion: Functional nutrients including Gln, Cr picolinate, Vit C, Bet, and Tau at the supplemental levels used in this study decrease stress responses of broiler chickens to a relatively similar extent. However, this reduction in stress responses could not fully ameliorate decreased productive performance of broiler chickens raised under the current heat stress conditions.